„wymienię wzrok na dotyk”. Poetyka oglądu w twórczości Tadeusza Różewicza - Cieślak, Robert (Przestrzenie Teorii, 2014)
The author poses the question of the importance of a sensory experience in Tadeusz Różewicz’s poetry, including the possibility of the co-existence of and/or replacement of the dominant sense of sight by that of touch. In poetic practice, this change is expressed by the metaphor “touching sight”. Phenomenological analysis allows one to determine the cognitive order in which the perception of an image precedes the perception of a word. The author argues that the understanding of poetry as the philosophy of art requires establishing a list of recalls of images and reconstructing cognitive order (including the subjective experience of space), which together create the “poetics of view”. When interpreted from this perspective, poetry can be treated as testimony to the knowledge of reality.